Peace education and Physical Education: Inclusive practices associated with values in Elementary School I - Kaiut , João Paulo; Dias , Juliane Rocio Quirino; Filho , Nei Alberto Salles; Tavares, Carolina Paioli (Seven Editora, 2024)
Physical Education has a primary function in school inclusion, promoting cultural diversity and interaction between students through varied body practices, capable of developing physical skills, the discipline can address in a practical way human values, Olympic and Paralympic values, going beyond the physical aspect and contributing to an inclusive and holistic education. Reviewing practice, seeking new pedagogical strategies is essential for the teaching-learning process in search of an inclusive environment. The present report aimed to apply inclusive pedagogical activities in Physical Education classes that aim at human values from the perspective of Education for Peace. For Callado (2004), peace education is a continuous process of education of values, which are manifested through the behavior of people or social groups. The pedagogical practice is characterized, in terms of purposes, as exploratory and qualitative, for which the following study themes were used as a bibliographic reference: Paralympic Modalities; Paralympic Values; Human Values; Cooperative Games. This work was developed in Physical Education classes in two different schools. The first being the Profª. Zahira Catta Preta Mello and had practice in an inclusive way, based on collaborative teaching, applying the contents of the curricular components focused in a transversal way to human values from the perspective of education for peace and activities. For the 1st cycle students, the practices were: Paralympic athletics, adapted bocce. On the other hand, the students of the 2nd cycle experienced the thematic unit sports through wheelchair basketball, goalball, wheelchair handball, sitting volleyball and poster making. In the second school, Dona Dilma Mafra School, it was applied to four classes of the 5th grade of elementary school, activities of games and games with a focus on the cooperative aspect, common good of the team, friendship, respect and excellence. In addition to sports activities adapted with rules that would allow emphasizing educational values, such as joy of effort, fair play, pursuit of excellence, and respect for others. The present research brought through the practice in Physical Education the vision of the student's development beyond intellectual capacities, expanding the discussion about human and educational values, in the bias of Education for Peace, in terms of seeing the student as an evolving being and valuing feelings and emotions, taking into account that education is carried out in different instances. However, it is concluded that the students in this period experienced the sports modalities and understood the importance of collaboration, cooperation and human values for a more inclusive society promoting education for peace. DOI:https://doi.org/10.56238/sevened2024.009-003